PENINGKATAN KEMAMPUAN MENULIS TEKS DISKUSI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE DEBAT PADA SISWA KELAS VIII H SMP NEGERI 1 REJANG LEBONG - Ernawaty Ernawaty; Elinas Yetti; Hapitriani Hapitriani (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2019)
The research objective is to know students’ ability in writing discussion text of class VIII H SMP Negeri 1 Rejang Lebong by applying debate in cooperative learning. This is a classroom action research with two cycles. Every cycle consists of planning, doing, observing, and reflecting. The data was collected through writing tests and observation on teacher and students' activities while teaching and learning occurred. The result of this research shows that there is a significant increase in students’ ability in writing discussion texts through debate. It can be seen from the average score of cycle 1 is 68,59 with the sufficient category and the classical achievement is 45,71%. It increases in cycle II 77,74 with good category and the classical achievement is 82,35%. In addition, using this model can also increase students' and teacher activities in looking for ideas in writing discussion text.